(untitled) (The International Journal for Scientific Research, 2025)
This research presents an analytical study of the interpretive narrations found in Al-Mustadrak ’ala al-Sahihayn by Imam al-Hakim al-Nisaburi, using Surah al-Fatihah as a case study. The inductive-analytical method was employed, whereby the interpretive narrations related to Surah al-Fatihah were collected, examined in terms of their chains of transmission (isnad) and texts (matn), and studied according to the principles of hadith and tafsir (exegesis). These narrations were also compared with other sources of tafsir, such as Jami’ al-Bayan by al-Tabari, Tafsir Ibn Kathir, and Musnad Ahmad. The research aims to determine the scholarly value of the narrations included by al-Hakim in his interpretation of Surah al-Fatihah, and to demonstrate their conformity with hadith and tafsir standards. It also highlights the role of al-Dhahabi in authenticating or critiquing these narrations. Furthermore, it seeks to uncover the underlying epistemological framework of these narrations and to elucidate the doctrinal and linguistic backgrounds that influence the understanding of the surah’s meanings. The results show that some of the narrations in al-Mustadrak are at the crossroads between acceptance and rejection, necessitating their re-evaluation in light of the development of hadith science and the need to connect them to the context of contemporary thematic and epistemological tafsir. The research offered recommendations to pay attention to neglected exegetical narrations and to revise them according to precise scientific principles.